PEMANFAATAN BENDA CAGAR BUDAYA DALAM PEMBELAJARAN SEJARAH DI SMA - Sutrisno Mohamad (Universitas Negeri Gorontalo, 2019)
This research aims to know the use of cultural heritage objects as a source of historical learning in Bolaang Mongondow, in addition to looking at the factors that become obstacles in the use of cultural heritage objects. The method used is a qualitive method to describe descriptively the phenomena that occur as whole and through. Data analysis used is interactive analysis, where the data collection or interaction. This research is expected that historical learning in school will utilize cultural heritage objects in the region to provide a complete historical understanding of events that occur in te region so that students are more familiar and love their region through cultural relics.